Cover Image. Issue 3 (4th April 2022) - Forlenza, Gregory P.; Ekhlaspour, Laya; DiMeglio, Linda A.; Fox, Larry A.; Rodriguez, Henry; Shulman, Dorothy I.; Kaiserman, Kevin B.; Liljenquist, David R.; Shin, John; Lee, Scott W.; Buckingham, Bruce A.
Abstract : The cover image is based on the Brief Report Glycemic outcomes of children 2‐6 years of age with type 1 diabetes during the pediatric MiniMed™ 670G system trial by Gregory P. Forlenza et al., https://doi.org/10.1111/pedi.13312 .